2013
DOI: 10.1002/da.22170
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality Predicts Treatment Outcome in CBT for Social Anxiety Disorder

Abstract: Background Sleep quality may be an important, yet relatively neglected, predictor of treatment outcome in cognitive-behavioral therapy (CBT) for anxiety disorders. Specifically, poor sleep quality may impair memory consolidation of in-session extinction learning. We therefore examined sleep quality as a predictor of treatment outcome in CBT for social anxiety disorder and the impact of d-cycloserine (DCS) on this relationship. Methods One hundred sixty-nine participants with a primary diagnosis of DSM-IV gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 27 publications
4
40
0
Order By: Relevance
“…Not only previous studies have supported the application of mindfulness-based stress reduction in patients with this disorder (12)(13)(14)(15)(16)(17)(18)(19) but also therapists have supported CBT in patients improvement (20)(21)(22). Furthermore, some studies have investigated MBSR versus CBT (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Not only previous studies have supported the application of mindfulness-based stress reduction in patients with this disorder (12)(13)(14)(15)(16)(17)(18)(19) but also therapists have supported CBT in patients improvement (20)(21)(22). Furthermore, some studies have investigated MBSR versus CBT (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been replicated in a recent study that used virtual-reality exposure therapy for DSM-IV diagnosed Spider Phobia (Kleim et al, 2013). Yet more recently, a large study of cognitive behavioral therapy in Social Anxiety Disorder has shown that better self-reported baseline sleep was associated with better post-treatment outcome on measures of anxiety (Zalta et al, 2013). Therefore, the memory enhancing function of sleep might be exploited to strengthen therapeutic extinction learned in exposure-based therapy by using strategically timed sleep bouts (Kleim et al, 2013; Pace-Schott, Verga, et al, 2012a).…”
Section: Related Clinical Findingsmentioning
confidence: 99%
“…One study demonstrated that afternoon naps as short as 1.5 hours immediately following successful exposure therapy for spider phobia resulted in significantly lower reported levels of distress and catastrophic cognitions at one-week follow-up [47]. Additionally, more restful sleep following CBT sessions for social anxiety disorder was associated with larger symptom reductions at subsequent sessions [48]. Mirroring findings in basic extinction learning paradigms [46], reducing the time interval between exposure therapy and sleep also enhances treatment outcomes.…”
Section: Past and More Recent Workmentioning
confidence: 99%